2021
DOI: 10.35473/ijm.v4i2.1185
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Pengetahuan tentang Anemia dan Dukungan Keluarga terhadap Kepatuhan Konsumsi Tablet Tambah Darah pada Remaja Putri di SMPN 01 Brondong Lamongan

Abstract: Anemia

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The Correlation Between Knowledge of Young Women and Compliance with Iron Supplement Tablet Consumption The results of the Spearman test show no significant relationship between the level of adolescent knowledge and compliance with iron supplements at SMPN 01 Long Bagun, p (0.256 > 0.05). This is in line with research conducted by Ningtyas et al (2021) (10); the measured experimental results obtained were p = 0.414 > 0.05. This is similar to research conducted by Lismiana & Indarjo (2021) (11) with the results that there was no relationship between knowledge about anemia and iron supplement tablets and adolescent girls' compliance in consuming iron supplement tablets where p = 0.93 (p> 0.05).…”
Section: Discussionsupporting
confidence: 93%
“…The Correlation Between Knowledge of Young Women and Compliance with Iron Supplement Tablet Consumption The results of the Spearman test show no significant relationship between the level of adolescent knowledge and compliance with iron supplements at SMPN 01 Long Bagun, p (0.256 > 0.05). This is in line with research conducted by Ningtyas et al (2021) (10); the measured experimental results obtained were p = 0.414 > 0.05. This is similar to research conducted by Lismiana & Indarjo (2021) (11) with the results that there was no relationship between knowledge about anemia and iron supplement tablets and adolescent girls' compliance in consuming iron supplement tablets where p = 0.93 (p> 0.05).…”
Section: Discussionsupporting
confidence: 93%
“…This result is supported by Ningtyas's research, which obtained a P value of 0.414 > 0.05, so it can be concluded that there is no difference in compliance between respondents who have good, sufficient, and poor knowledge of consuming iron tablets, meaning that Ha is rejected and Ho is accepted. So, there is no significant relationship between the level of knowledge and compliance with iron tablet consumption (Ningtyas et al, 2021). The results of the previous research, with Kendall Tau correlation coefficient were -0.181 with a significance number of 0.155, so there was no relationship between attitudes of young women about anemia and the behavior of consuming iron tablets (Sulistyorini and Maesaroh, 2019).…”
Section: Level Of Knowledge About Anemia Menstrual Patterns and Adher...mentioning
confidence: 87%
“…Results from other studies showed that there was no significant difference between obedient and nonadherent female students in taking iron tablets. According to Ningtyas et al (2021), 39 respondents (54.9%) were compliant in taking iron supplements, while 32 respondents (45.1%) were not. The level of knowledge about anemia in adolescents at a public senior high school in Magelang was measured using a questionnaire.…”
Section: Level Of Knowledge About Anemia Menstrual Patterns and Adher...mentioning
confidence: 99%
“…Berdasarkan hasil penelitian (Zulaekah, 2018) diketahui terjadinya peningkatan pengetahuan anak dan orang tua tentang masalah anemia dengan ratarata nilai sebelum diberikan intervensi sebesar 54,11 ± 17,74 dan sesudah diberikan intervensi edukasi adalah 71,56 ± 12,52 sehingga terjadi peningkatan sebesar 17,44. Pendidikan kesehatan dapat membuat klien yang sebelumnya belum tahu menjadi lebih tahu karena individu mendapatkan informasi dan pengetahuan baru (Ningtyas et al, 2021).…”
Section: Hasil Dan Diskusiunclassified
“…Selain itu, pangan yang yang bisa dikonsumsi dari sayuran yaitu mengkonsumsi sayuran hijau. Dapat diartikan dengan pengetahuan yang dimiliki oleh ekluarga tentang bahan makanan yang tinggi akan zat gizi akan membantu pencegahan terjadinya anemia pada remaja (Ningtyas et al, 2021).…”
Section: Hasil Dan Diskusiunclassified